Amalgamation and Auckland city: A New Zealand success story?. Issue 4 (13th November 2020) - Asquith, Andy; McNeill, Jeffrey; Stockley, Elizabeth
Abstract: The amalgamation of Auckland's local authorities in 2010 was remarkable for New Zealand. It created a city‐region to address perceived failures arising from trying to coordinate and align leadership and strategic planning while maintaining political accountability within a fractured local government system. The factors leading up to the Royal Commission on Auckland Governance in 2009 and its findings that led to amalgamation are examined and the Commission's report and its implementation are addressed. Finally, an assessment is made of the operation of the newly created Auckland Council during its first 9 years. Crucial to the amalgamation process was a change of national government, which had a very different political philosophy of the role of (local) government than its predecessor. Despite a difficult start, the Council achieved two of its three initial criteria: creating leadership for Auckland and providing strategic direction for New Zealand's biggest city. Abstract : The amalgamation in local government in Auckland, New Zealand in 2010 saw a very different political philosophy towards the role, scope, and scale of the country's local government. Despite a difficult start, the Council has managed to achieve two of its three initial criteria: creating leadership for Auckland and providing strategic direction for New Zealand's biggest city.